Dual-wavelength passively Q-switched erbium-doped fiber laser with MWCNTs slurry as a saturable absorber - Zuikafly, S.N.F.; Ahmad, F.; Ibrahim, M.H.; Latiff, A.A.; Harun, Sulaiman Wadi (Photonics Society of Poland, 2016)
In this work, a compact, stable dual-wavelength Q-switched laser has been demonstrated, with a multi-walled carbon nanotubes (MWCNTs) slurry as a saturable absorber (SA) which is independent of any host polymer. The MWCNTs slurry is fabricated and the peak shift is investigated using Raman spectroscopy.The passively Q-switched erbium-doped fiber laser (EDFL) oscillated simultaneously at 1532.32nm and 1556.97nm with 24.67nm peak separation, at threshold and maximum input power of 26mW and 74mW, respectively. By increasing the input pump power from 36mW to 74mW, the pulse train repetition rate increases from 25kHz to 78kHz, while the pulse width is reduced from 17.84μs to 5.24μs. The generated pulse produced maximum pulse energy and maximum peak power of 11.97nJ and 2.05mW, respectively at maximum input pump power. The recorded signal to noise ratio is about 62dB and shows that the proposed MWCNTs slurry based SA is able to generate dual wavelength Q-switched pulse laser with a high stability pulse.